Effect of sieving methodolgy on determining particle size of ground corn, sorghum, and wheat by sieving - Kalivoda, Julie (Kansas State University, 2016)
Experiments were conducted to evaluate particle size methodology and flow-ability of fractionated corn. The first experiment compared five variations of the current approved method to determine geometric mean diameter (d[subscript]gw) and geometric standard deviation (S[subscript]gw) described by ANSI/ASAE S319.4 “Method of determining and expressing fineness of feed materials by sieving”. This method controls many variables, including the suggested sample size and the type, number, and size of sieves. However, the method allows for variations in sieving time, sieve agitator inclusion, and the use of dispersing agent. The variations were tested with three grains (corn, wheat, and sorghum). There was no method × grain (P>0.05) interaction for d[subscript]gw, so it was removed. Ten minute sieving time with sieve agitators and dispersing agent resulted in the lowest d[subscript]gw and greatest S[subscript]gw (P<0.05). The second experiment evaluated particle size analysis on ground corn using a 3-sieve method with varying sieving time (30, 60, and 90 s) with the addition of dispersing agent. The sieving time for the 3-sieve method referred to the time sieves were hand shaken side to side. Ninety seconds sieving time with dispersing agent (0.25 g) resulted in the lowest d[subscript]gw (P<0.05). The 3-sieve method was not developed to calculate the S[subscript]gw, so means and main effects were not determined. Experiment three evaluated particle size and flow-ability by grinding corn at two moisture (10 and 12%) with three screenings levels (0, 2.5, and 5%). Results suggested cleaning corn prior to grinding with a roller mill does not change particle size or flow-ability. Experiment four continued the evaluation of flow-ability with corn ground to three target particle sizes (400, 500, and 600 µm) and fractionated into fine, medium, and coarse segments. Target particle size impacted d[subscript]gw, S[subscript]gw, and bulk density (P<0.05), prior to fractionation. Based on the results of this experiment, flow-ability can be improved if fine particles (<282 µm) are removed. Results of these experiments indicated that particle size analysis should use sieve agitators, dispersing agent, and 10 or 15 min sieving time for the standard 13-sieve method and 90 s sieving time with dispersing agent for the 3-sieve method.
Keywords: particle size; feed; flow ability; corn; methodologygrain